Steel material
Patent Information
- Application Number
- JP2023149654
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-03-27
Smart Images

Figure 2025042555000001 
Figure 2025042555000002 
Figure 2025042555000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to steel products, and more particularly to steel products used in CO2 storage technology. [Background technology]
[0002] Currently, the rise in carbon dioxide (CO2) concentrations on land has become a global problem. As a result, efforts to curb CO2 emissions are underway. Among these efforts to curb CO2 emissions, CCUS in particular has been attracting attention.
[0003] CCUS is an abbreviation for Carbon dioxide Capture, Utilization and Storage. In other words, CCUS includes three technologies: capture, utilization, and storage of CO2. Of these, a technology that stores CO2 has been attracting attention, which involves capturing CO2 emitted from industrial facilities such as power plants and factories, and injecting the CO2 into depleted oil wells for storage.
[0004] Steel materials used in such CO2 storage technologies are required to have a yield strength of, for example, 80 ksi class (552 to 655 MPa). To date, a steel material having a yield strength of 80 ksi class has been proposed in JP 2002-115028 A (Patent Document 1).
[0005] The steel material disclosed in Patent Document 1 is a steel pipe for oil wells, characterized in that it has a yield stress YS of 552 MPa (80 ksi) or more and an L-direction absorbed energy E (J) at 0°C that satisfies the formula (E≧-0.4169×YS+480). Patent Document 1 discloses that this steel material can withstand crushing caused by strong external pressure from the outside, which is required for casings. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2002-115028 A Summary of the Invention [Problem to be solved by the invention]
[0007] As described above, in carbon dioxide (CO2) storage technology, captured CO2 is injected into depleted oil wells and stored. Meanwhile, trace amounts of hydrogen sulfide may be contained in the atmosphere near the bottom of depleted oil wells. Here, in a sour environment containing hydrogen sulfide, there is a concern that sulfide stress cracking may occur due to the stress applied to steel materials. Therefore, steel materials expected to be applied to CO2 storage technology are also required to have sulfide stress cracking resistance (hereinafter referred to as SSC resistance). However, the above Patent Document 1 does not consider the SSC resistance of steel materials at all.
[0008] An object of the present disclosure is to provide a steel material that combines an 80 ksi-class (552 to less than 655 MPa) yield strength with excellent SSC resistance. [Means for solving the problem]
[0009] The steel material according to this embodiment is In mass%, C: 0.26-0.35%, Si: 0.10 to 1.00%, Mn: 0.90-1.40%, P: 0.015% or less, S: 0.0020% or less, Cr: 0.15~0.50%, Mo: 0.05-0.25%, sol.Al: 0.001~0.070%, N: 0.0010~0.0080%, V: 0~0.60%, Nb: 0-0.03%, Ti: 0 to 0.05%, W: 0 to 0.50%, Zr: 0 to 0.005%, Co: 0 to 0.500%, Ni: 0 to 0.300%, Cu: 0-0.500%, Sn: 0~0.100%, Ca: 0 to 0.0035%, Mg: 0 to 0.0035%, B: 0~0.0010%, Rare earth elements: 0 to 0.0050%, and The balance is composed of Fe and impurities, and satisfies formula (1); The yield strength is less than 552 to 655 MPa, In the steel material, The prior austenite grain size is defined as D, When the Mn content in the vicinity of the prior austenite grain boundary is defined as [Mn], the P content in the vicinity of the prior austenite grain boundary is defined as [P], and the Mo content in the vicinity of the prior austenite grain boundary is defined as [Mo], The D, the [Mn], the [P], and the [Mo] satisfy formula (2). 0.045≦Mo / Mn≦0.200 (1) -0.0851×D-[Mn]-3×[P]+[Mo]≧-13.1 (2) Here, the element symbols in formula (1) are substituted with the contents of the corresponding elements in mass%, the prior austenite grain size is substituted for D in formula (2) in μm, the Mn content in the vicinity of the prior austenite grain boundaries is substituted for [Mn] in formula (2) in mol%, the P content in the vicinity of the prior austenite grain boundaries is substituted for [P] in formula (2) in mol%, and the Mo content in the vicinity of the prior austenite grain boundaries is substituted for [Mo] in formula (2) in mol%. Effect of the Invention
[0010] The steel material according to the present disclosure can achieve both an 80 ksi-class (552 to less than 655 MPa) yield strength and excellent SSC resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] First, the inventors of the present invention investigated the possibility of obtaining a steel material having a yield strength of 80 ksi (552 to less than 655 MPa) in anticipation of its application to carbon dioxide (CO2) storage technology. In other words, the inventors of the present invention investigated and examined a method of obtaining an 80 ksi-class yield strength and excellent SSC resistance in a steel material anticipated for application to CO2 storage technology. As a result, the inventors of the present invention obtained the following findings.
[0012] First, the inventors of the present invention focused on the chemical composition and investigated how to obtain a steel material having an 80 ksi-class yield strength and excellent SSC resistance. It has been known that molybdenum (Mo) forms fine carbides to increase the strength of steel materials. Therefore, if the Mo content is too high, the strength of the steel material becomes too high, and there is a possibility that an 80 ksi-class yield strength cannot be obtained. Therefore, the inventors of the present invention specifically attempted to obtain an 80 ksi-class yield strength stably by setting the Mo content in the range of 0.05 to 0.25%.
[0013] On the other hand, Mo enhances the hardenability of steel material. Therefore, there is a concern that the hardenability of steel material may be reduced by reducing the Mo content to the range of 0.05 to 0.25%. Therefore, the present inventors considered increasing the manganese (Mn) content instead of Mo to enhance the hardenability of steel material. As a result of the inventors' investigation, it was found that, specifically, if the Mn content is increased to the range of 0.90 to 1.40%, the hardenability of steel material can be stably obtained even with 0.05 to 0.25% Mo.
[0014] In consideration of the above findings, the present inventors have determined that the alloy contains, in mass %, C: 0.26-0.35%, Si: 0.10-1.00%, Mn: 0.90-1.40%, P: 0.015% or less, S: 0.0020% or less, Cr: 0.15-0.50%, Mo: 0.05-0.25%, sol.Al: 0.001-0.070%, N: 0.0010-0.0080%, V: 0-0.60%, Nb: 0-0.03%, Ti: 0-0.05%, W: 0.15-0.50%, Mo: 0.05-0.25%, sol.Al: 0.001-0.070%, It was thought that a steel material consisting of the following composition: Cu: 0~0.50%, Zr: 0~0.005%, Co: 0~0.500%, Ni: 0~0.300%, Cu: 0~0.500%, Sn: 0~0.100%, Ca: 0~0.0035%, Mg: 0~0.0035%, B: 0~0.0010%, rare earth elements: 0~0.0050%, and the balance: Fe and impurities could potentially achieve both 80 ksi-class yield strength and excellent SSC resistance.
[0015] On the other hand, even in the case of steel materials having the above-mentioned chemical composition, there are cases where both 80 ksi-class yield strength and excellent SSC resistance cannot be achieved. Therefore, the present inventors further investigated the relationship between strength and SSC resistance for steel materials having the above-mentioned chemical composition in detail. As a result, it was revealed that in steel materials having the above-mentioned chemical composition, if the chemical composition further satisfies the following formula (1), both 80 ksi-class yield strength and excellent SSC resistance can be achieved, provided that the other configurations of this embodiment are satisfied. 0.045≦Mo / Mn≦0.200 (1) Here, the element symbols in formula (1) are substituted with the contents of the corresponding elements in mass %.
[0016] Fn1 is defined as Mo / Mn. Fn1 is an index showing the balance between the strength and SSC resistance of a steel material having the above-mentioned chemical composition. If Fn1 is too low, the SSC resistance of the steel material decreases. On the other hand, if Fn1 is too high, the strength of the steel material becomes too high, and an 80 ksi-class yield strength cannot be obtained. Therefore, the steel material according to this embodiment has Fn1 of 0.045 to 0.200, on the premise that the above-mentioned chemical composition is satisfied. As a result, the steel material according to this embodiment can achieve both an 80 ksi-class yield strength and excellent SSC resistance, on the condition that the other configurations of this embodiment are satisfied.
[0017] Next, the inventors of the present invention have investigated various methods for improving the SSC resistance of a steel material having the above-mentioned chemical composition including formula (1) and a yield strength of 80 ksi class. As a result, it has been revealed that in a steel material having the above-mentioned chemical composition including formula (1) and yield strength, embrittlement of the prior austenite grain boundaries in the steel material is likely to become apparent. In other words, in a steel material having the above-mentioned chemical composition including formula (1) and yield strength, if the prior austenite grain boundaries can be strengthened, there is a possibility that excellent SSC resistance can be obtained while maintaining the yield strength of 80 ksi class. Hereinafter, in this specification, prior austenite grains are also referred to as "prior γ grains".
[0018] Furthermore, the inventors have conducted detailed studies on a method for strengthening prior γ grain boundaries in a steel material having the above-mentioned chemical composition including formula (1) and having a yield strength of 80 ksi class. Specifically, in the above-mentioned steel material, Mn and P in the vicinity of the prior γ grain boundaries embrittle the prior γ grain boundaries, while Mo in the vicinity of the prior γ grain boundaries strengthens the prior γ grain boundaries. In other words, if the Mn and P contents in the vicinity of the prior γ grain boundaries are reduced and the Mo content in the vicinity of the prior γ grain boundaries is increased, the SSC resistance of the steel material may be improved.
[0019] On the other hand, as described above, in the steel material according to the present embodiment, the Mo content is reduced and the Mn content is increased to ensure hardenability. That is, in the steel material having the above-mentioned chemical composition including formula (1), the Mn content near the prior γ grain boundary is likely to be high and the Mo content near the prior γ grain boundary is likely to be low. Therefore, the present inventors have studied further strengthening of the prior γ grain boundary. As a result, it has become clear that in the above-mentioned steel material, the SSC resistance of the steel material can be improved while maintaining the yield strength of 80 ksi class by adjusting not only the Mn content, P content, and Mo content near the prior γ grain boundary but also the prior austenite grain size. Hereinafter, in this specification, the prior austenite grain size is also referred to as the "prior γ grain size D". If the prior γ grain size D is reduced, the area occupied by the prior γ grain boundary in the steel material increases, and embrittlement of the prior γ grain boundary is likely to be alleviated.
[0020] As a result of detailed investigations by the present inventors taking into consideration the above findings, it has become clear that in steel having the above-mentioned chemical composition including formula (1), if the prior γ grain size D, the Mn content [Mn] near the prior γ grain boundaries, the P content [P] near the prior γ grain boundaries, and the Mo content [Mo] near the prior γ grain boundaries satisfy the following formula (2), then it is possible to stably achieve both 80 ksi-class yield strength and excellent SSC resistance. -0.0851×D-[Mn]-3×[P]+[Mo]≧-13.1 (2) Here, in equation (2), D is substituted with the prior γ grain size in μm, [Mn] is substituted with the Mn content in the vicinity of the prior γ grain boundary in mol%, [P] is substituted with the P content in the vicinity of the prior γ grain boundary in mol%, and [Mo] is substituted with the Mo content in the vicinity of the prior γ grain boundary in mol%.
[0021] Hereinafter, the Mn content [Mn] near the prior γ grain boundary is also referred to as the "grain boundary Mn content [Mn]", the P content [P] near the prior γ grain boundary is also referred to as the "grain boundary P content [P]", and the Mo content [Mo] near the prior γ grain boundary is also referred to as the "grain boundary Mo content [Mo]". Here, Fn2 is defined as -0.0851 x D - [Mn] - 3 x [P] + [Mo]. Fn2 is an index showing the degree of strengthening of the prior γ grain boundary in a steel material having the above-mentioned chemical composition including formula (1). If Fn2 is too small, the prior γ grain boundary is not strengthened sufficiently, and the SSC resistance of the steel material is not sufficiently improved. On the other hand, if Fn2 is -13.1 or more, the prior γ grain boundary is sufficiently strengthened, and the steel material can achieve both 80 ksi-class yield strength and excellent SSC resistance. Therefore, on the premise that the above-mentioned chemical composition is satisfied, the steel material according to this embodiment has Fn1 of 0.045 to 0.200 and Fn2 of -13.1 or more. As a result, the steel material according to this embodiment can stably achieve both 80 ksi-class yield strength and excellent SSC resistance.
[0022] The gist of the steel material according to this embodiment, which was completed based on the above findings, is as follows.
[0023] [1] A steel material, In mass%, C: 0.26-0.35%, Si: 0.10 to 1.00%, Mn: 0.90-1.40%, P: 0.015% or less, S: 0.0020% or less, Cr: 0.15~0.50%, Mo: 0.05-0.25%, sol.Al: 0.001~0.070%, N: 0.0010~0.0080%, V: 0~0.60%, Nb: 0-0.03%, Ti: 0 to 0.05%, W: 0 to 0.50%, Zr: 0 to 0.005%, Co: 0 to 0.500%, Ni: 0 to 0.300%, Cu: 0-0.500%, Sn: 0~0.100%, Ca: 0 to 0.0035%, Mg: 0 to 0.0035%, B: 0~0.0010%, Rare earth elements: 0 to 0.0050%, and The balance is composed of Fe and impurities, and satisfies formula (1); The yield strength is less than 552 to 655 MPa, In the steel material, The prior austenite grain size is defined as D, When the Mn content in the vicinity of the prior austenite grain boundary is defined as [Mn], the P content in the vicinity of the prior austenite grain boundary is defined as [P], and the Mo content in the vicinity of the prior austenite grain boundary is defined as [Mo], The D, the [Mn], the [P], and the [Mo] satisfy formula (2); Steel material. 0.045≦Mo / Mn≦0.200 (1) -0.0851×D-[Mn]-3×[P]+[Mo]≧-13.1 (2) Here, the element symbols in formula (1) are substituted with the contents of the corresponding elements in mass%, the prior austenite grain size is substituted for D in formula (2) in μm, the Mn content in the vicinity of the prior austenite grain boundaries is substituted for [Mn] in formula (2) in mol%, the P content in the vicinity of the prior austenite grain boundaries is substituted for [P] in formula (2) in mol%, and the Mo content in the vicinity of the prior austenite grain boundaries is substituted for [Mo] in formula (2) in mol%.
[0024] [2] The steel material according to [1], V: 0.01 to 0.60%, Nb: 0.01 to 0.03%, Ti: 0.01 to 0.05%, W: 0.01 to 0.50%, Zr: 0.001 to 0.005%, Co: 0.001 to 0.500%, Ni: 0.001 to 0.300%, Cu: 0.001 to 0.500%, Sn: 0.001~0.100%, Ca: 0.0001 to 0.0035%, Mg: 0.0001 to 0.0035%, B: 0.0001 to 0.0010%, and Rare earth elements: 0.0001 to 0.0050%, containing one or more elements selected from the group consisting of Steel material.
[0025] [3] The steel material according to [1] or [2], The steel material is a steel pipe. Steel material.
[0026] The shape of the steel material according to this embodiment is not particularly limited. The steel material according to this embodiment may be a steel pipe, a round bar (solid material), or a steel plate. The round bar means a steel bar having a circular cross section perpendicular to the axial direction. The steel pipe may be a seamless steel pipe or a welded steel pipe.
[0027] The steel material according to this embodiment will be described in detail below. "%" for elements means mass % unless otherwise specified.
[0028] [Chemical composition] The chemical composition of the steel material according to this embodiment contains the following elements.
[0029] C: 0.26-0.35% Carbon (C) improves the hardenability of steel material and increases the strength of the steel material. If the C content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the C content is too high, even if the contents of other elements are within the range of this embodiment, carbides are excessively generated in the steel material, and the SSC resistance of the steel material decreases. Therefore, the C content is 0.26 to 0.35%. The preferred lower limit of the C content is 0.27%, more preferably 0.28%, and more preferably 0.29%. The preferred upper limit of the C content is 0.34%, more preferably 0.33%, and more preferably 0.32%.
[0030] Silicon: 0.10 to 1.00% Silicon (Si) deoxidizes steel. If the Si content is too low, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Si content is too high, the SSC resistance of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Si content is 0.10 to 1.00%. The preferred lower limit of the Si content is 0.12%, more preferably 0.14%, and even more preferably 0.15%. The preferred upper limit of the Si content is 0.95%, more preferably 0.90%, more preferably 0.80%, more preferably 0.70%, and even more preferably 0.60%.
[0031] Mn: 0.90-1.40% Manganese (Mn) improves the hardenability of steel material and increases the strength of the steel material. If the Mn content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Mn content is too high, the grain boundary Mn amount [Mn] becomes too high. As a result, even if the contents of other elements are within the range of this embodiment, the SSC resistance of the steel material decreases. Therefore, the Mn content is 0.90 to 1.40%. The preferred lower limit of the Mn content is 0.95%, more preferably 1.00%, and more preferably 1.05%. The preferred upper limit of the Mn content is 1.39%, more preferably 1.35%, and more preferably 1.30%.
[0032] P:0.015% or less Phosphorus (P) is an impurity. That is, the lower limit of the P content is more than 0%. If the P content is too high, the grain boundary P content [P] becomes too high. As a result, even if the contents of other elements are within the range of this embodiment, the SSC resistance of the steel material decreases. Therefore, the P content is 0.015% or less. The preferred upper limit of the P content is 0.014%, more preferably 0.013%. The P content is preferably as low as possible. However, an extreme reduction in the P content significantly increases the manufacturing cost. Therefore, in consideration of industrial production, the preferred lower limit of the P content is 0.001%, more preferably 0.002%, and even more preferably 0.003%.
[0033] S: 0.0020% or less Sulfur (S) is an impurity. That is, the lower limit of the S content is more than 0%. If the S content is too high, even if the contents of other elements are within the range of this embodiment, coarse sulfide-based inclusions are generated, and the SSC resistance of the steel material decreases. Therefore, the S content is 0.0020% or less. A preferred upper limit of the S content is 0.0019%, more preferably 0.0018%, and even more preferably 0.0016%. The S content is preferably as low as possible. However, an extreme reduction in the S content significantly increases the manufacturing cost. Therefore, in consideration of industrial production, a preferred lower limit of the S content is 0.0001%, more preferably 0.0002%, and even more preferably 0.0003%.
[0034] Cr: 0.15~0.50% Chromium (Cr) improves the hardenability of steel material and increases the strength of the steel material. If the Cr content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Cr content is too high, the strength of the steel material becomes too high even if the contents of other elements are within the range of this embodiment, and the desired strength cannot be obtained. Therefore, the Cr content is 0.15 to 0.50%. The preferred lower limit of the Cr content is 0.18%, and more preferably 0.20%. The preferred upper limit of the Cr content is 0.45%, and more preferably 0.40%.
[0035] Mo: 0.05 to 0.25% Molybdenum (Mo) forms fine carbides to increase the strength of the steel material. Mo also increases the hardenability of the steel material. Mo also concentrates at the prior γ grain boundaries and contributes to grain boundary strengthening. If the Mo content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Mo content is too high, even if the contents of other elements are within the range of this embodiment, fine carbides are excessively generated, and the strength of the steel material becomes too high, and the desired strength cannot be obtained. Therefore, the Mo content is 0.05 to 0.25%. The preferred lower limit of the Mo content is 0.06%, and more preferably 0.07%. The preferred upper limit of the Mo content is 0.24%, and more preferably 0.20%, and more preferably 0.18%.
[0036] Sol.Al: 0.001~0.070% Aluminum (Al) deoxidizes steel. If the Al content is too low, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Al content is too high, coarse oxide-based inclusions are generated, and the SSC resistance of the steel material decreases, even if the contents of other elements are within the range of this embodiment. Therefore, the Al content is 0.001 to 0.070%. The preferred lower limit of the Al content is 0.005%, and more preferably 0.010%. The preferred upper limit of the Al content is 0.065%, and more preferably 0.060%. The "Al" content in this specification means the content of "acid-soluble Al", that is, "sol.Al".
[0037] N: 0.0010~0.0080% Nitrogen (N) forms nitrides and reduces the prior γ grain size D of the steel material by the pinning effect. As a result, Fn2 increases, and the SSC resistance of the steel material increases. If the N content is too low, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the N content is too high, coarse nitrides are generated and the SSC resistance of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the N content is 0.0010 to 0.0080%. The preferred lower limit of the N content is 0.0015%, more preferably 0.0020%, and even more preferably 0.0025%. The preferred upper limit of the N content is 0.0075%, and even more preferably 0.0070%.
[0038] The balance of the chemical composition of the steel material according to the present embodiment is composed of Fe and impurities. Here, the term "impurities" refers to substances that are mixed in from raw materials such as ore and scrap, or from the manufacturing environment, during industrial production of the steel material, and that are permissible within a range that does not adversely affect the steel material according to the present embodiment.
[0039] [Optional element] The chemical composition of the above-mentioned steel material may further contain one or more elements selected from the group consisting of V, Nb, Ti, W, and Zr in place of a portion of Fe. All of these elements are optional elements, and increase the temper softening resistance of the steel material and increase the strength of the steel material.
[0040] V: 0~0.60% Vanadium (V) is an optional element and may not be contained. That is, the V content may be 0%. When it is contained, V generates fine carbides during tempering, which increases the temper softening resistance of the steel material and increases the strength of the steel material. If even a small amount of V is contained, the above effect can be obtained to a certain extent. However, if the V content is too high, the SSC resistance of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the V content is 0 to 0.60%. The preferable lower limit of the V content is more than 0%, more preferably 0.01%, more preferably 0.02%, more preferably 0.04%, and more preferably 0.06%. The preferable upper limit of the V content is 0.57%, more preferably 0.45%, and more preferably 0.40%.
[0041] Nb: 0 to 0.03% Niobium (Nb) is an optional element and may not be contained. That is, the Nb content may be 0%. When Nb is contained, Nb forms fine carbides during tempering to increase the temper softening resistance of the steel material and increase the strength of the steel material. If even a small amount of Nb is contained, the above effects can be obtained to a certain extent. However, if the Nb content is too high, even if the contents of other elements are within the range of this embodiment, excessive carbonitrides and the like are generated, and the SSC resistance of the steel material decreases. Therefore, the Nb content is 0 to 0.03%. The preferable lower limit of the Nb content is more than 0%, more preferably 0.01%, and more preferably 0.02%. The preferable upper limit of the Nb content is less than 0.03%.
[0042] Ti: 0 to 0.05% Titanium (Ti) is an optional element and may not be contained. That is, the Ti content may be 0%. When contained, Ti forms fine carbides to increase the temper softening resistance of the steel material and increase the strength of the steel material. If even a small amount of Ti is contained, the above effects can be obtained to a certain extent. However, if the Ti content is too high, even if the contents of other elements are within the range of this embodiment, coarse nitrides are generated and the SSC resistance of the steel material decreases. Therefore, the Ti content is 0 to 0.05%. The preferred lower limit of the Ti content is more than 0%, more preferably 0.01%, and more preferably 0.02%. The preferred upper limit of the Ti content is less than 0.05%, and more preferably 0.04%.
[0043] W: 0~0.50% Tungsten (W) is an optional element and may not be contained. That is, the W content may be 0%. When W is contained, W forms fine carbides during tempering to increase the temper softening resistance of the steel material and increase the strength of the steel material. If even a small amount of W is contained, the above effects can be obtained to a certain extent. However, if the W content is too high, even if the contents of other elements are within the range of this embodiment, coarse carbides are formed and the SSC resistance of the steel material decreases. Therefore, the W content is 0 to 0.50%. The preferred lower limit of the W content is more than 0%, more preferably 0.01%, and more preferably 0.02%. The preferred upper limit of the W content is 0.45%, and more preferably 0.40%.
[0044] Zr: 0 to 0.005% Zirconium (Zr) is an optional element and may not be contained. That is, the Zr content may be 0%. When contained, Zr forms fine carbides during tempering to increase the temper softening resistance of the steel material and increase the strength of the steel material. If even a small amount of Zr is contained, the above effects can be obtained to a certain extent. However, if the Zr content is too high, even if the contents of other elements are within the range of this embodiment, coarse oxides are generated and the SSC resistance of the steel material decreases. Therefore, the Zr content is 0 to 0.005%. The preferable lower limit of the Zr content is more than 0%, more preferably 0.001%, and more preferably 0.002%. The preferable upper limit of the Zr content is less than 0.005%, and more preferably 0.004%.
[0045] The chemical composition of the steel material described above may further contain one or more elements selected from the group consisting of Co and Ni in place of a portion of Fe. All of these elements are optional elements, and improve the hardenability and strength of the steel material.
[0046] Co: 0 to 0.500% Cobalt (Co) is an optional element and may not be contained. That is, the Co content may be 0%. When contained, Co enhances the hardenability of the steel material and enhances the strength of the steel material. If even a small amount of Co is contained, the above effect can be obtained to some extent. However, if the Co content is too high, even if the contents of other elements are within the range of this embodiment, the hardenability of the steel material is rather reduced, and the strength of the steel material is reduced. Therefore, the Co content is 0 to 0.500%. The preferred lower limit of the Co content is more than 0%, more preferably 0.001%, more preferably 0.010%, more preferably 0.030%, and more preferably 0.050%. The preferred upper limit of the Co content is 0.450%, and more preferably 0.400%.
[0047] Ni: 0 to 0.300% Nickel (Ni) is an optional element and may not be contained. That is, the Ni content may be 0%. When contained, Ni enhances the hardenability of the steel material and enhances the strength of the steel material. Even if even a small amount of Ni is contained, these effects can be obtained to a certain extent. However, if the Ni content is too high, even if the contents of other elements are within the range of this embodiment, local corrosion is promoted and the SSC resistance of the steel material is reduced. Therefore, the Ni content is 0 to 0.300%. The preferred lower limit of the Ni content is more than 0%, more preferably 0.001%, more preferably 0.010%, and more preferably 0.030%. The preferred upper limit of the Ni content is 0.250%, and more preferably 0.200%.
[0048] The chemical composition of the above-mentioned steel material may further contain one or more elements selected from the group consisting of Cu and Sn in place of a portion of Fe. All of these elements are optional elements and increase the strength of the steel material.
[0049] Cu: 0 to 0.500% Copper (Cu) is an optional element and may not be contained. That is, the Cu content may be 0%. When contained, Cu increases the strength of the steel material. If even a small amount of Cu is contained, the above effect can be obtained to some extent. However, if the Cu content is too high, even if the contents of other elements are within the range of this embodiment, the strength of the steel material becomes too high, and the SSC resistance of the steel material decreases. Therefore, the Cu content is 0 to 0.500%. The preferred lower limit of the Cu content is more than 0%, more preferably 0.001%, more preferably 0.010%, more preferably 0.030%, and more preferably 0.050%. The preferred upper limit of the Cu content is 0.450%, more preferably 0.400%, and more preferably 0.350%.
[0050] Sn: 0 to 0.100% Tin (Sn) is an optional element and may not be contained. That is, the Sn content may be 0%. When contained, Sn increases the strength of the steel material. If even a small amount of Sn is contained, the above effect can be obtained to a certain extent. However, if the Sn content is too high, the hot workability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Sn content is 0 to 0.100%. The preferred lower limit of the Sn content is more than 0%, more preferably 0.001%, more preferably 0.002%, and more preferably 0.003%. The preferred upper limit of the Sn content is 0.095%, more preferably 0.090%, and more preferably less than 0.090%.
[0051] The chemical composition of the above-mentioned steel material may further contain, instead of a part of Fe, one or more elements selected from the group consisting of Ca, Mg, B, and rare earth elements. All of these elements are optional elements, and improve the hot workability of the steel material.
[0052] Ca: 0 to 0.0035% Calcium (Ca) is an optional element and may not be contained. That is, the Ca content may be 0%. When contained, Ca renders S in the steel material harmless as sulfides and improves the hot workability of the steel material. If even a small amount of Ca is contained, the above effect can be obtained to a certain extent. However, if the Ca content is too high, even if the contents of other elements are within the range of this embodiment, coarse oxides are generated and the SSC resistance of the steel material decreases. Therefore, the Ca content is 0 to 0.0035%. The preferred lower limit of the Ca content is more than 0%, more preferably 0.0001%, more preferably 0.0003%, more preferably 0.0006%, and more preferably 0.0010%. The preferred upper limit of the Ca content is 0.0033%, and more preferably 0.0030%.
[0053] Magnesium: 0 to 0.0035% Magnesium (Mg) is an optional element and may not be contained. That is, the Mg content may be 0%. When contained, Mg renders S in the steel material harmless as sulfides, and improves the hot workability of the steel material. If even a small amount of Mg is contained, the above effect can be obtained to a certain extent. However, if the Mg content is too high, even if the contents of other elements are within the range of this embodiment, coarse oxides are generated, and the SSC resistance of the steel material decreases. Therefore, the Mg content is 0 to 0.0035%. The preferable lower limit of the Mg content is more than 0%, more preferably 0.0001%, more preferably 0.0003%, more preferably 0.0006%, and more preferably 0.0010%. The preferable upper limit of the Mg content is 0.0033%, and more preferably 0.0030%.
[0054] B: 0~0.0010% Boron (B) is an optional element and may not be contained. That is, the B content may be 0%. When contained, B enhances the hardenability of the steel material. If even a small amount of B is contained, the above effect can be obtained to some extent. However, if the B content is too high, even if the contents of other elements are within the range of this embodiment, coarse nitrides are generated, and the SSC resistance of the steel material decreases. Therefore, the B content is 0 to 0.0010%. The preferred lower limit of the B content is more than 0%, more preferably 0.0001%, and more preferably 0.0002%. The preferred upper limit of the B content is 0.0009%, and more preferably 0.0008%.
[0055] Rare earth elements (REM): 0~0.0050% Rare earth elements (REM) are optional elements and may not be contained. That is, the REM content may be 0%. When contained, REM renders S in the steel harmless as sulfides, and improves the hot workability of the steel. If even a small amount of REM is contained, the above effect can be obtained to some extent even if the contents of other elements are within the range of this embodiment. However, if the REM content is too high, coarse oxides are generated and the SSC resistance of the steel decreases even if the contents of other elements are within the range of this embodiment. Therefore, the REM content is 0 to 0.0050%. The preferred lower limit of the REM content is more than 0%, more preferably 0.0001%, more preferably 0.0003%, and more preferably 0.0006%. The preferred upper limit of the REM content is 0.0045%, and more preferably 0.0040%.
[0056] In this specification, REM refers to one or more elements selected from the group consisting of scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and the lanthanides lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. In addition, in this specification, the REM content refers to the total content of these elements.
[0057] [Formula (1)] The steel material according to this embodiment satisfies the following formula (1), provided that the above-mentioned chemical composition is satisfied. 0.045≦Mo / Mn≦0.200 (1) Here, the element symbols in formula (1) are substituted with the contents of the corresponding elements in mass %.
[0058] Fn1 (=Mo / Mn) is an index showing the balance between the strength and SSC resistance of a steel material having the above-mentioned chemical composition. If Fn1 is too low, the SSC resistance of the steel material decreases. On the other hand, if Fn1 is too high, the strength of the steel material becomes too high, and an 80 ksi-class yield strength cannot be obtained. Therefore, the steel material according to this embodiment has Fn1 of 0.045 to 0.200, on the premise that the above-mentioned chemical composition is satisfied. As a result, the steel material according to this embodiment can achieve both an 80 ksi-class yield strength and excellent SSC resistance, on the condition that the other configurations of this embodiment are satisfied.
[0059] In this embodiment, the preferred lower limit of Fn1 is 0.048, more preferably 0.050, and even more preferably 0.053. The preferred upper limit of Fn1 is 0.195, more preferably 0.190, and even more preferably 0.185. In this embodiment, Fn1 (=Mo / Mn) is calculated by rounding off the obtained numerical value to the fourth decimal place.
[0060] [Yield strength] The yield strength of the steel material according to this embodiment is 552 to less than 655 MPa (80 ksi class, 80 to less than 95 ksi). The yield strength in this specification means the 0.2% offset yield strength (MPa) obtained by a tensile test at room temperature (24±3°C) in accordance with ASTM E8 / E8M (2021).
[0061] In this embodiment, the yield strength of the steel material can be determined by the following method. Specifically, a tensile test is performed by a method conforming to ASTM E8 / E8M (2021). A round bar test piece is prepared from the steel material according to this embodiment. When the steel material is a steel plate, the round bar test piece is prepared from the center of the plate thickness. In this case, the axial direction of the round bar test piece is parallel to the rolling direction of the steel plate. When the steel material is a steel pipe, the round bar test piece is prepared from the center of the wall thickness. In this case, the axial direction of the round bar test piece is parallel to the axial direction of the steel pipe. When the steel material is a round steel, the round bar test piece is prepared from the R / 2 position. In this case, the axial direction of the round bar test piece is parallel to the axial direction of the round steel. In this specification, the R / 2 position means the center position of the radius R in a cross section perpendicular to the axial direction of the round steel. The size of the round bar test piece is, for example, a parallel part diameter of 6 mm and a gauge length of 30 mm. A tensile test is performed using a round bar test piece at room temperature (24±3°C) in the air, and the obtained 0.2% offset proof stress (MPa) is defined as the yield strength (MPa). In this embodiment, the yield strength (MPa) is a value obtained by rounding off the obtained numerical value to the first decimal place.
[0062] [Formula (2)] The steel material according to this embodiment satisfies the above-mentioned chemical composition and, on the premise that Fn1 satisfies 0.045 to 0.200, satisfies the following formula (2). -0.0851×D-[Mn]-3×[P]+[Mo]≧-13.1 (2) Here, in formula (2), D is substituted with the prior gamma grain size in μm, [Mn] is substituted with the Mn content in the vicinity of the prior gamma grain boundary in mol%, [P] is substituted with the P content in the vicinity of the prior gamma grain boundary in mol%, and [Mo] is substituted with the Mo content in the vicinity of the prior gamma grain boundary in mol%. As described above, in this specification, the Mn content [Mn] in the vicinity of the prior gamma grain boundary is also referred to as the "grain boundary Mn content [Mn]", the P content [P] in the vicinity of the prior gamma grain boundary is also referred to as the "grain boundary P content [P]", and the Mo content [Mo] in the vicinity of the prior gamma grain boundary is also referred to as the "grain boundary Mo content [Mo]".
[0063] Fn2 (=-0.0851×D-[Mn]-3×[P]+[Mo]) is an index showing the degree of strengthening of the prior γ grain boundary in the steel material having the above-mentioned chemical composition including formula (1). If Fn2 is too small, the prior γ grain boundary is not strengthened sufficiently, and the SSC resistance of the steel material is not sufficiently improved. On the other hand, if Fn2 is -13.1 or more, the prior γ grain boundary is sufficiently strengthened, and the steel material can achieve both 80 ksi-class yield strength and excellent SSC resistance. Therefore, the steel material according to this embodiment has Fn1 of 0.045 to 0.200 and Fn2 of -13.1 or more, on the premise that the above-mentioned chemical composition is satisfied. As a result, the steel material according to this embodiment can stably achieve both 80 ksi-class yield strength and excellent SSC resistance.
[0064] As described above, the steel material according to the present embodiment has a reduced Mo content and an increased Mn content. Therefore, the grain boundary Mo content [Mo] is likely to be low, and the grain boundary Mn content [Mn] is likely to be high. That is, in a steel material having the above-mentioned chemical composition, embrittlement of the prior γ grain boundary is likely to become apparent. On the other hand, when the prior γ grain size D of a steel material having the above-mentioned chemical composition is small, the area of the prior γ grain boundary increases, and embrittlement of the prior γ grain boundary is likely to be suppressed. Therefore, in the present embodiment, not only the grain boundary Mo content [Mo] that strengthens the prior γ grain boundary, and the grain boundary Mn content [Mn] and grain boundary P content [P] that embrittle the prior γ grain boundary are reduced, but also the prior γ grain size D that contributes to the area of the prior γ grain boundary is adjusted. As a result, the prior γ grain boundary can be sufficiently strengthened even in a steel material having the above-mentioned chemical composition including formula (1).
[0065] In this embodiment, the preferred lower limit of Fn2 is −13.0, more preferably −12.5, more preferably −12.0, and even more preferably −11.8. The upper limit of Fn2 is not particularly limited, and may be, for example, 0.0, −1.0, −2.0, or −3.0.
[0066] In the steel material according to the present embodiment, the prior γ grain size D, the grain boundary Mn content [Mn], the grain boundary P content [P], and the grain boundary Mo content [Mo] are not particularly limited as long as they satisfy the formula (2). The upper limit of the prior γ grain size D may be, for example, 200.0 μm, 180.0 μm, 150.0 μm, or 125.0 μm. The prior γ grain size D is preferably small. However, in the steel material having the above-mentioned chemical composition, the prior γ grain boundary can be strengthened by satisfying Fn2 of -13.1 or more even if the lower limit of the prior γ grain size D is, for example, 10.0 μm, 20.0 μm, 30.0 μm, or 40.0 μm.
[0067] The upper limit of the grain boundary Mn content [Mn] may be, for example, 5.0 mol.%, 4.0 mol.%, or 3.0 mol.%. The grain boundary Mn content [Mn] is preferably low. However, when the above-mentioned chemical composition is used, the grain boundary Mn content [Mn] may be, for example, 1.0 mol.% or more, or 1.5 mol.% or more. Even in this case, the prior γ grain boundaries can be strengthened by satisfying Fn2 of -13.1 or more.
[0068] The upper limit of the grain boundary P content [P] may be, for example, 4.0 mol.%, 3.0 mol.%, or 2.5 mol.%. The grain boundary P content [P] is preferably low. However, when the above-mentioned chemical composition is used, the grain boundary P content [P] may be, for example, 0.1 mol.% or more, or 0.3 mol.% or more. Even in this case, the prior γ grain boundaries can be strengthened by satisfying Fn2 of -13.1 or more.
[0069] The lower limit of the grain boundary Mo content [Mo] may be, for example, 0.5 mol.%, 1.0 mol.%, or 1.5 mol.%. The grain boundary Mo content [Mo] is preferably high. However, when the above-mentioned chemical composition is used, the grain boundary Mo content [Mo] may be, for example, 5.0 mol.% or less, or 4.0 mol.% or less. Even in this case, the prior γ grain boundaries can be strengthened by satisfying Fn2 of -13.1 or more.
[0070] In this embodiment, Fn2 can be obtained by the following method. First, the prior γ grain size D of the steel material according to this embodiment is obtained. Specifically, a test piece for measuring the prior γ grain size D is prepared from the steel material according to this embodiment. When the steel material is a steel plate, a test piece is prepared from the center of the plate thickness, with a surface including the rolling direction and the plate thickness direction as the observation surface. When the steel material is a steel pipe, a test piece is prepared from the center of the plate thickness, with a surface including the pipe axial direction and the pipe radial direction as the observation surface. When the steel material is a round bar, a test piece is prepared that includes the R / 2 position in the center and has a surface including the axial direction and the radial direction as the observation surface.
[0071] The test piece is embedded in resin, and the observation surface is polished to a mirror finish. It is then immersed for about 60 seconds in a solution of saturated aqueous picric acid mixed with an appropriate amount of surfactant, and the prior γ grain boundaries are revealed by etching. The area of the observation surface is not limited, but for example, 100 mm 2 (10 mm x 10 mm). The grain size number G is obtained based on a cutting method in accordance with JIS G 0551 (2020) by optical microscope observation. The obtained grain size number G is converted to an average grain size M (μm) based on the following formulas (3) and (4). In this embodiment, the average grain size M obtained by the above method is defined as a prior γ grain size D (μm). In other words, in this embodiment, the prior austenite grain size D (μm) means the average grain size (μm) of prior austenite grains obtained based on a cutting method in accordance with JIS G 0551 (2020). n=2 G+3 (3) M=1000 / n 1 / 2 (4)
[0072] Next, the grain boundary Mn content [Mn], grain boundary P content [P], and grain boundary Mo content [Mo] of the steel material according to this embodiment are obtained. Specifically, a notched round bar test piece is prepared from the steel material according to this embodiment. When the steel material is a steel plate, the test piece is prepared from the center of the plate thickness. In this case, the axial direction of the test piece is parallel to the rolling direction of the steel plate. When the steel material is a steel pipe, the test piece is prepared from the center of the wall thickness. In this case, the axial direction of the test piece is parallel to the axial direction of the steel pipe. When the steel material is a round steel, the test piece is prepared from the R / 2 position. In this case, the axial direction of the test piece is parallel to the axial direction of the round steel. The notch is formed in the center of the axial length of the round bar test piece, and the size of the notched round bar test piece is, for example, 3 mm in diameter and 17 mm in axial length. Furthermore, the notch portion is, for example, a V-notch shape with a depth of 0.7 mm, and is formed around the entire circumference of the round bar.
[0073] The prepared test piece was placed in a vacuum chamber attached to the Auger electron spectrometer, and the degree of vacuum in the chamber was set to 10 -7 Pa or less. For example, a JAMP-9500F manufactured by JEOL Ltd. is used as the Auger electron spectrometer. A test piece cooled to -120°C or less in a chamber is subjected to impact fracture to obtain a prior γ grain boundary fracture surface. In this embodiment, a plurality of measurement points are identified from each of a plurality of prior γ grain boundary fracture surfaces. Specifically, for example, three measurement points are identified from each of three prior γ grain boundary fracture surfaces, for a total of nine measurement points. In addition, the measurement points identify areas of the prior γ grain boundary fracture surfaces other than precipitates. Whether or not there are precipitates can be determined from the contrast by a person skilled in the art.
[0074] The element concentration analysis is performed on the specified measurement points by Auger electron spectroscopy. In the Auger electron spectroscopy, the acceleration voltage is 10 kV, the sample current is 10 nA, and the target elements are quantified as P, S, C, Cr, Fe, Mn, Si, and Mo. In the differential Auger spectrum, the Auger peaks of each element used for quantitative calculation are P: 102 to 130 eV, S: 131 to 165 eV, C: 234 to 292 eV, Cr: 510 to 540 eV, Fe: 685 to 715 eV, Mn: 535 to 545 eV, Si: 1588 to 1640 eV, and Mo: 169 to 199 eV. The quantitative value is obtained for the obtained Auger peak of each element using the peak intensity and the relative sensitivity coefficient. At this time, the peak intensity is obtained as the difference between the maximum value and the minimum value of the peak (so-called peak-to-peak intensity). Moreover, the relative sensitivity coefficient can be a value provided by the device manufacturer.
[0075] For each measurement point, the Mn content (mol.%) when the total content of P, S, C, Cr, Fe, Mn, Si, and Mo is 100 mol.% is defined as the Mn content (mol.%) at that measurement point. The arithmetic average value of the Mn contents (mol.%) at all measurement points is defined as the grain boundary Mn content [Mn] (mol.%). Similarly, for each measurement point, the P content (mol.%) when the total content of P, S, C, Cr, Fe, Mn, Si, and Mo is 100 mol.% is defined as the P content (mol.%) at that measurement point. The arithmetic average value of the P content (mol.%) at all measurement points is defined as the grain boundary P content [P] (mol.%). Furthermore, for each measurement point, the Mo content (mol.%) when the total content of P, S, C, Cr, Fe, Mn, Si, and Mo is 100 mol.% is defined as the Mo content (mol.%) at that measurement point. The arithmetic mean value of the Mo content (mol%) at all measurement points is defined as the grain boundary Mo content [Mo] (mol%).
[0076] That is, in this embodiment, the Mn content [Mn] in the vicinity of the prior austenite grain boundary means the Mn content (mol.%) when the total content of P, S, C, Cr, Fe, Mn, Si, and Mo, which are quantified by Auger electron spectroscopy at the prior austenite grain boundary fracture surface, is taken as 100 mol.%. Similarly, the P content [P] in the vicinity of the prior austenite grain boundary means the arithmetic average value of the P content (mol.%) when the total content of P, S, C, Cr, Fe, Mn, Si, and Mo, which are quantified by Auger electron spectroscopy at the prior austenite grain boundary fracture surface, is taken as 100 mol.%. Furthermore, the Mo content [Mo] in the vicinity of the prior austenite grain boundary means the Mo content (mol.%) when the total content of P, S, C, Cr, Fe, Mn, Si, and Mo, which are quantified by Auger electron spectroscopy at the prior austenite grain boundary fracture surface, is taken as 100 mol.%.
[0077] In this embodiment, the prior γ grain size D (μm), the grain boundary Mn content [Mn] (mol%), the grain boundary P content [P] (mol%), and the grain boundary Mo content [Mo] (mol%) are all calculated by rounding off the first decimal place of the obtained numerical value. Furthermore, in this embodiment, Fn2 (=-0.0851×D-[Mn]-3×[P]+[Mo]) is also calculated by rounding off the first decimal place of the obtained numerical value.
[0078] [SSC resistance] The steel material according to the present embodiment has the above-mentioned chemical composition, satisfies formula (1) and also satisfies formula (2). As a result, the steel material according to the present embodiment has both an 80 ksi-class yield strength and excellent SSC resistance. In the present embodiment, excellent SSC resistance is defined as follows.
[0079] In this embodiment, the SSC resistance is evaluated by an SSC resistance test performed in accordance with NACE TM0177-2016 Method A. Specifically, a 5.0 mass% sodium chloride aqueous solution (NACE solution A) adjusted to pH 2.7 with acetic acid is used as the test solution. A round bar test piece is prepared from the steel material according to this embodiment. When the steel material is a steel plate, a round bar test piece having an axial direction parallel to the rolling direction of the steel plate is prepared from the center of the plate thickness. When the steel material is a steel pipe, a round bar test piece having an axial direction parallel to the pipe axis direction of the steel pipe is prepared from the center of the wall thickness. When the steel material is a round steel, a round bar test piece having an axial direction parallel to the axial direction of the round steel is prepared from the R / 2 position. The size of the round bar test piece is, for example, a diameter of 6.35 mm and a length of the parallel part of 25.4 mm.
[0080] A stress equivalent to 90% of the actual yield stress is applied to the prepared round bar test piece. A test solution at 24°C is poured into a test vessel so that the stressed round bar test piece is immersed in the test solution to form a test bath. After degassing the test bath, 1 atm of H2S gas is blown into the test bath to saturate the test bath. The test bath saturated with H2S gas is maintained at 24°C for 720 hours. In the SSC resistance test carried out under the above conditions, no cracks were observed in the steel material according to this embodiment after 720 hours.
[0081] [Microstructure] The microstructure of the steel material according to the present embodiment is mainly composed of tempered martensite and tempered bainite. Specifically, the microstructure of the steel material according to the present embodiment has a total volume fraction of tempered martensite and tempered bainite of 90% or more. The remainder of the microstructure is, for example, ferrite or pearlite. A steel material that satisfies the above-mentioned chemical composition including formula (1), a yield strength of less than 552 to 655 MPa, and an Fn2 of -13.1 or more has excellent SSC resistance when it has a microstructure in which the total volume fraction of tempered martensite and tempered bainite is 90% or more. Therefore, in the present embodiment, if a steel material that satisfies the above-mentioned chemical composition including formula (1), a yield strength of less than 552 to 655 MPa, and an Fn2 of -13.1 or more has excellent SSC resistance, the microstructure of the steel material is determined to have a total volume fraction of tempered martensite and tempered bainite of 90% or more.
[0082] When the volume fractions of tempered martensite and tempered bainite are determined by observation, they can be determined by the following method. First, a test piece having a specific observation surface is prepared from the steel material according to this embodiment. When the steel material is a steel plate, a test piece is prepared from the center of the plate thickness, with a surface including the rolling direction and the plate thickness direction as the observation surface. When the steel material is a steel pipe, a test piece is prepared from the center of the plate thickness, with a surface including the pipe axial direction and the pipe radial direction as the observation surface. When the steel material is a round bar, a test piece is prepared that includes the R / 2 position in the center, with a surface including the axial direction and the radial direction as the observation surface.
[0083] After polishing the observation surface of the test piece to a mirror finish, it is immersed in a nital etching solution for about 10 seconds to reveal the structure by etching. The etched observation surface is observed in 10 fields of view using a SEM with secondary electron images. The field area is, for example, 0.01 mm 2(magnification 1000x). In each field of view, tempered martensite and tempered bainite are identified from the contrast. The area ratios of the identified tempered martensite and tempered bainite are determined. The method for determining the area ratios is not particularly limited, and any known method may be used. For example, the area ratios of tempered martensite and tempered bainite can be determined by image analysis. In this embodiment, the arithmetic average value of the area ratios of tempered martensite and tempered bainite determined in all fields of view is defined as the volume ratios of tempered martensite and tempered bainite.
[0084] [Manufacturing method] A method for manufacturing a steel material according to this embodiment will be described below. A method for manufacturing a seamless steel pipe will be described below as an example of the steel material according to this embodiment. The method for manufacturing a seamless steel pipe includes a step of preparing a mother pipe (preparation step), and a step of quenching and tempering the mother pipe to produce a seamless steel pipe (quenching step and tempering step). Note that the manufacturing method according to this embodiment is not limited to the manufacturing method described below. Each step will be described in detail below.
[0085] [Preparation process] In the preparation step, an intermediate steel material having the above-mentioned chemical composition is prepared. As long as the intermediate steel material has the above-mentioned chemical composition, the method for manufacturing the intermediate steel material is not particularly limited. The intermediate steel material referred to here is a plate-shaped steel material when the final product is a steel plate, and is a blank pipe when the final product is a steel pipe.
[0086] The preparation step may include a step of preparing a material (material preparation step) and a step of hot working the material to produce an intermediate steel material (hot working step). Hereinafter, the case including the material preparation step and the hot working step will be described in detail.
[0087] [Material preparation process] In the material preparation step, a material is manufactured using molten steel having the above-mentioned chemical composition. The method for manufacturing the material is not particularly limited and may be a well-known method. Specifically, a cast piece (slab, bloom, or billet) may be manufactured using the molten steel by a continuous casting method. An ingot may be manufactured using the molten steel by an ingot casting method. If necessary, the slab, bloom, or ingot may be rolled to manufacture a billet. The material (slab, bloom, or billet) is manufactured by the above steps.
[0088] [Hot processing process] In the hot working process, the prepared material is hot worked to produce an intermediate steel material. When the steel material is a seamless steel pipe, the intermediate steel material corresponds to a mother pipe. First, the billet is heated in a heating furnace. The heating temperature is not particularly limited, but is, for example, 1100 to 1300°C. The billet extracted from the heating furnace is hot worked to produce a mother pipe (seamless steel pipe). The method of hot working is not particularly limited, and may be a well-known method.
[0089] For example, the Mannesmann process may be carried out as the hot working to produce a mother pipe. In this case, a round billet is pierced and rolled using a piercing machine. When piercing and rolling is performed, the piercing ratio is not particularly limited, but is, for example, 1.0 to 4.0. The pierced and rolled round billet is further hot rolled using a mandrel mill, a reducer, a sizing mill, or the like to produce a mother pipe. The cumulative reduction in area in the hot working process is, for example, 20 to 70%.
[0090] Other hot working methods may be used to produce a mother pipe from the billet. For example, in the case of a short, thick-walled steel material such as a coupling, the mother pipe may be produced by forging using the Erhardt method or the like. The mother pipe is produced by the above steps. The thickness of the mother pipe is not particularly limited, but is, for example, 9 to 60 mm.
[0091] When the steel material is round steel, the material is first heated in a heating furnace. The heating temperature is not particularly limited, but is, for example, 1100 to 1300°C. The material extracted from the heating furnace is subjected to hot processing to produce an intermediate steel material having a circular cross section perpendicular to the axial direction. The hot processing is, for example, blooming rolling by a blooming mill, or hot rolling by a continuous rolling mill. In the continuous rolling mill, a horizontal stand having a pair of grooved rolls arranged side by side in the vertical direction and a vertical stand having a pair of grooved rolls arranged side by side in the horizontal direction are alternately arranged.
[0092] When the steel material is a steel plate, the material is first heated in a heating furnace. The heating temperature is not particularly limited, but is, for example, 1100 to 1300° C. The material removed from the heating furnace is subjected to hot rolling using a blooming mill and a continuous rolling mill to produce an intermediate steel material in the shape of a steel plate.
[0093] The mother pipe produced by hot working may be air-cooled (as-rolled). The mother pipe produced by hot working may be quenched directly after the hot working without being cooled to room temperature, or may be quenched after being reheated after the hot working.
[0094] When quenching is performed directly after hot working, or after reheating, cooling may be stopped or slow cooling may be performed during quenching. In this case, it is possible to prevent quench cracks from occurring in the mother pipe. When quenching is performed directly after hot working, or after reheating, stress relief annealing (SR) may be performed after quenching and before the next heat treatment. In this case, residual stress in the mother pipe is removed.
[0095] As described above, in the preparation step, an intermediate steel material is prepared. The intermediate steel material may be manufactured by the above-mentioned preferred step, or an intermediate steel material manufactured by a third party, or an intermediate steel material manufactured in a factory or business establishment other than the factory where the quenching step and tempering step described below are performed, may be prepared. The quenching step will be described in detail below.
[0096] [Quenching process] In the quenching process, quenching is performed on a prepared intermediate steel material (blank pipe). In this specification, "quenching" means rapidly cooling an intermediate steel material having an A3 point or higher. Here, in this specification, the temperature of the intermediate steel material immediately before rapid cooling when quenching is performed is also referred to as the quenching temperature. Preferably, in the quenching process, the quenching temperature is 800 to 1000°C. If the quenching temperature is too high, the prior γ grain size D may become too large. Therefore, the quenching temperature is preferably 800 to 1000°C.
[0097] In quenching, the intermediate steel material (blank tube) is continuously cooled to continuously lower the surface temperature of the blank tube. The method of continuous cooling is not particularly limited and may be a well-known method. For example, the method of continuous cooling is a method of immersing the blank tube in a water tank for cooling, or a method of accelerating cooling the blank tube by shower water cooling or mist cooling.
[0098] If the cooling rate during quenching is too slow, the microstructure will not be mainly martensite and bainite, and the mechanical properties specified in this embodiment will not be obtained. Here, in the quenching process according to this embodiment, the average cooling rate in the range of the surface temperature of the intermediate steel material (raw pipe) during quenching from 800 to 500°C is defined as the cooling rate during quenching CR 800-500 Specifically, the cooling rate during quenching, CR 800-500 is determined from the temperature measured at the slowest cooling location in the cross section of the intermediate steel being quenched (e.g., the center of the intermediate steel thickness when both surfaces are forced cooled).
[0099] In the quenching step according to the present embodiment, the preferred cooling rate during quenching is CR 800-500 The cooling rate during quenching is preferably 60°C / min or more. 800-500 The lower limit of the cooling rate during quenching is 300° C. / min, and more preferably 600° C. / min. 800-500 The upper limit of the quenching rate is not particularly specified, but is, for example, 6000° C. / min. Through the above steps, the quenching process according to this embodiment can be carried out. The tempering process will be described in detail below.
[0100] [Tempering process] In the tempering process, tempering is performed after the above-mentioned quenching. In this specification, "tempering" refers to the process of tempering the intermediate steel material after quenching. c1 It means that the steel is reheated to a temperature below the specified temperature and then held at that temperature. Preferably, in the tempering process according to the present embodiment, heating is performed at a two-stage heating rate, the steel is held at a specific temperature, and then cooled at a two-stage cooling rate.
[0101] In the steel material having the above-mentioned chemical composition, the temperature at which the diffusion of Mo is most promoted thermodynamically is T[Mo MAX In the tempering process according to the present embodiment, the residence time in the temperature range below T1 (°C) and the temperature range above T1 (°C) defined by the following formula (B) is controlled. T[Mo MAX ]=510+150×C+50×Si+440×Mo (A) T1=T[Mo MAX ]+20 (B) Here, the element symbols in formula (A) are substituted with the contents of the corresponding elements in mass%. MAX ] is in °C, and T1 in formula (B) is in °C.
[0102] Specifically, the temperature range of 500°C to T1 (°C) is a temperature range where the diffusion of Mn and P is more likely to occur than the diffusion of Mo. Therefore, in the temperature range of 500°C to T1 (°C), relatively rapid heating and cooling are preferable. In this case, the diffusion of Mn and P is suppressed, and the grain boundary Mn amount [Mn] and the grain boundary P amount [P] can be reduced. On the other hand, the temperature range of T1 (°C) or higher is a temperature range where the diffusion of Mo is more likely to occur than the diffusion of Mn and P. Therefore, in the temperature range of T1 (°C) or higher, relatively slow heating and cooling are preferable. In this case, the diffusion of Mo is promoted, and the grain boundary Mo amount [Mo] can be increased. Hereinafter, the heating step, the holding step, and the cooling step in the tempering step according to this embodiment will be specifically described in detail.
[0103] [Heating process] Preferably, in the heating step of the tempering process according to the present embodiment, the quenched intermediate steel material (blank pipe) is heated at a two-stage heating rate. Specifically, in the heating step according to the present embodiment, the heating rate from 500 to T1 (°C) is set at HR 500-T1 (℃ / min), and the rate of temperature rise from T1 (℃) to the temperature T (℃) held in the holding step described later is defined as HR T1-T (℃), HR 500-T1 (℃ / min) and HR T1-T The temperature (° C. / min) is preferably in the following range: HR 500-T1 (℃ / min): 30℃ / min or more HR T1-T (℃ / min): 5 to less than 30℃ / min
[0104] As mentioned above, at 500°C to T1 (°C), the diffusion of Mn and P is more likely to occur than that of Mo. Therefore, in HR 500-T1 If the heating rate (°C / min) is too slow, the diffusion of Mn and P is promoted, and the grain boundary Mn content [Mn] and grain boundary P content [P] may not be reduced sufficiently. 500-T1 It is preferable to set the rate of diffusion to 30°C / min or more. As described above, at T1 (°C) or more, the diffusion of Mo is more likely to occur than the diffusion of Mn and P. Therefore, in the case of HR 500-T1 If the heating rate (°C / min) is too fast, the diffusion of Mo is not sufficiently promoted, and the grain boundary Mo content [Mo] may not be sufficiently increased. T1-T It is preferable to set the heating rate to 5 to less than 30° C. / min.
[0105] In addition, the heating rate HR 500-T1 (℃ / min) and heating rate HR T1-T The temperature rise rate (°C) can be measured by a known method. For example, the temperature rise rate can be calculated from the surface temperature of the intermediate steel material measured with a non-contact thermometer and the temperature rise time. The temperature rise rate in the heating step can be controlled by a known method. For example, it may be controlled by using a plurality of heat treatment furnaces for heating.
[0106] [Holding process] In the holding step, the intermediate steel material heated in the heating step is held at a holding temperature T (°C). The holding temperature T (°C) in the holding step is adjusted as appropriate depending on the chemical composition of the steel material and the yield strength to be obtained. In other words, the holding temperature T (°C) is adjusted for the intermediate steel material (blank pipe) having the chemical composition of this embodiment to adjust the yield strength of the steel material to 80 to less than 95 ksi (552 to less than 655 MPa). Here, the holding temperature T (°C) corresponds to the temperature of the furnace when the intermediate steel material is held. The holding time t (min) means the time from when the temperature of the intermediate steel material reaches a predetermined holding temperature to when it is extracted from the heat treatment furnace.
[0107] The holding temperature T (°C) is appropriately adjusted depending on the chemical composition of the steel and the yield strength to be obtained. That is, the holding temperature T is adjusted for an intermediate steel (blank pipe) having the chemical composition of this embodiment, so that the yield strength of the steel is adjusted to 552 to less than 655 MPa. In the tempering process according to this embodiment, the preferred holding temperature T is 640 to 720°C.
[0108] If the holding time t (min) is too short, a microstructure mainly composed of tempered martensite and tempered bainite may not be obtained. On the other hand, if the holding time is too long, the above effects are saturated. Therefore, in the holding step of this embodiment, the holding time t (min) is preferably set to 20 to 180 minutes.
[0109] [Cooling process] Preferably, in the cooling step of the tempering process according to the present embodiment, the intermediate steel material held in the holding step is cooled at a two-stage cooling rate. Specifically, in the cooling step according to the present embodiment, the cooling rate from the holding temperature T (°C) to T1 (°C) is set to CR T-T1 (℃), and the cooling rate from T1 (℃) to 500℃ is defined as CR T1-500 (℃ / min), CR T-T1 (℃ / min) and CR T1-500 The temperature (° C. / min) is preferably in the following range: CR T-T1 (℃ / min): 30~70℃ / min CR T1-500 (℃ / min): 70℃ / min or more
[0110] As mentioned above, above T1 (℃), the diffusion of Mo is more likely to occur than the diffusion of Mn and P. Therefore, in CR T-T1 If the heating rate (°C / min) is too fast, the diffusion of Mo is not sufficiently promoted, and the grain boundary Mo content [Mo] may not be sufficiently increased. T-T1 It is preferable to set the rate of diffusion to 30 to less than 70°C / min. As described above, in the range of T1 (°C) to 500°C, the diffusion of Mn and P is more likely to occur than the diffusion of Mo. Therefore, in the case of CR T1-500 If the heating rate (°C / min) is too slow, the diffusion of Mn and P is promoted, and the grain boundary Mn content [Mn] and grain boundary P content [P] may not be reduced sufficiently. T1-500 It is preferable to set the heating rate to 70° C. / min or more.
[0111] In addition, the cooling rate CR T-T1 (℃ / min) and cooling rate CR T1-500 The cooling rate (°C) can be measured by a known method. For example, the cooling rate can be calculated from the surface temperature of the intermediate steel material measured with a non-contact thermometer and the cooling time. The cooling rate in the cooling process can be controlled by a known method. For example, when cooling is performed using shower water cooling, the cooling rate may be controlled by adjusting the amount of water in the shower.
[0112] The steel material according to this embodiment can be manufactured by the above manufacturing method. In the above manufacturing method, a method for manufacturing a steel pipe has been described as one example. However, the steel material according to this embodiment may be a steel plate or other shape. Similar to the above manufacturing method, a manufacturing method for a steel plate or other shape also includes, for example, a preparation step, a quenching step, and a tempering step. Furthermore, the above manufacturing method is one example, and the steel material may be manufactured by other manufacturing methods.
[0113] The present invention will be described in more detail below with reference to examples. Note that the examples described below are examples of conditions adopted to confirm the feasibility and effects of the steel material according to this embodiment. In other words, the steel material according to this embodiment is not limited to the examples described below. EXAMPLES
[0114] 180 kg of molten steel having the chemical composition shown in Table 1-1 and Table 1-2 was produced. In Table 1-1 and Table 1-2, "-" means that the content of the corresponding element was at the impurity level. Specifically, the V content, Nb content, Ti content, and W content of Test No. 1 were 0% when rounded off to the third decimal place. The Zr content, Co content, Ni content, Cu content, and Sn content of Test No. 1 were 0% when rounded off to the fourth decimal place. The Ca content, Mg content, B content, and REM content of Test No. 1 were 0% when rounded off to the fifth decimal place. Table 1-2 shows the content of the elements of each test number and Fn1 (=Mo / Mn) calculated from the above definition.
[0115] [Table 1-1]
[0116] [Table 1-2]
[0117] A round billet was produced by continuous casting using the molten steel of each test number. The produced round billet of each test number was heated and hot worked. Specifically, the round billet of each test number was subjected to hot rolling by the Mannesmann-mandrel method as hot working to produce a blank pipe (seamless steel pipe) of each test number.
[0118] The obtained blank pipes of each test number were subjected to quenching and tempering. In the quenching process, the blank pipes of each test number were held at 950°C for 10 minutes and then water-cooled to perform quenching. At this time, the cooling rate during quenching of the blank pipes of each test number was CR 800-500 was in the range of 60 to 6000℃ / min.
[0119] Furthermore, the obtained blank tubes of each test number were subjected to tempering. First, the blank tubes of each test number except for test number 47 were subjected to two-stage heating. Specifically, for each test number, the T[Mo MAX ] (℃) and T1 (℃) are shown in Table 2. For each test number, the heating rate HR 500-T1 (℃ / min) and the heating rate HR from T1 (℃) to T (℃) T1-T (℃ / min). Note that for test number 47, T1 (℃) was too high, so two-stage heating could not be performed.
[0120] For each test number, the heating rate HR 500-T1 If (℃ / min) is 30℃ / min or more, refer to "HR 500-T1 In the "A (Appropriate)" column, the heating rate HR 500-T1 If (℃ / min) is less than 30℃ / min, refer to "HR 500-T1 In the " column, "S (Slow)" is written. Note that test number 49 is the temperature rise rate HR 500-T1 The heating rate HR for each test number was 15°C / min. T1-T If the temperature (℃ / min) is less than 5 to 30℃ / min, refer to "HR T1-T In the "A (Appropriate)" column, the heating rate HR T1-T If (℃ / min) is 30℃ / min or more, refer to "HR T1-T In the " column, "F (Fast)" is written. Note that test number 50 is the temperature rise rate HR T1-T The heating rate was 60°C / min. The heating rate was adjusted by using multiple heat treatment furnaces for heating. The heating rate was determined from the surface temperature of the blank tube of each test number, which was measured with a non-contact thermometer.
[0121] [Table 2]
[0122] A holding step was carried out on the heated blank tube of each test number, in which the blank tube was held at a holding temperature T (°C) for a holding time t (min). The holding temperature T (°C) and holding time t (min) for each test number are shown in the "T (°C)" column of Table 2, and the "t (min)" column of Table 2, respectively. The blank tube of each test number was further cooled at cooling rates CR from T (°C) to T1 (°C) shown in Table 2. T-T1 (℃ / min) and cooling rate CR from T1 (℃) to 500℃ T1-500 (℃ / min), two-stage cooling was performed. Note that for test number 47, T1 (℃) was too high, so two-stage cooling could not be performed.
[0123] For each test number, the cooling rate CR T-T1 If the temperature (℃ / min) is less than 30 to 70℃ / min, refer to "CR T-T1 On the other hand, the cooling rate CR T-T1 If the temperature (℃ / min) is 70℃ / min or more, refer to "CR T-T1 In the " column, "F (Fast)" is shown. Note that test number 51 is the cooling rate CR T-T1 The cooling rate was 100°C / min. For each test number, the cooling rate CR T1-500 If the temperature (℃ / min) is 70℃ / min or more, refer to "CR T1-500 On the other hand, the cooling rate CR T1-500 If the temperature (℃ / min) is less than 70℃ / min, refer to "CR T1-500 In the " column, "S (Slow)" is shown. Note that test number 52 is the cooling rate CR T1-500 The cooling rate was 40°C / min. The cooling rate was adjusted by adjusting the amount of water used for shower cooling. The cooling rate was determined from the surface temperature of the blank pipe of each test number, which was measured with a non-contact thermometer. Through the above manufacturing process, seamless steel pipes of each test number were obtained.
[0124] [Evaluation test] The seamless steel pipes having the respective test numbers after tempering were subjected to a tensile test, an Fn2 measurement test, and an SSC resistance evaluation test, which will be described below.
[0125] [Tensile test] A tensile test was performed on the seamless steel pipe of each test number in accordance with ASTM E8 / E8M (2021). Specifically, a round bar test piece with a parallel diameter of 6 mm and a gauge length of 30 mm was prepared from the center of the wall thickness of the seamless steel pipe of each test number. The axial direction of the round bar test piece was parallel to the pipe axial direction of the seamless steel pipe. Using the prepared round bar tensile test piece, a tensile test was performed at room temperature (25 ° C) in air to obtain the yield strength (MPa) of the seamless steel pipe of each test number. In this embodiment, the 0.2% offset proof stress (MPa) obtained in the tensile test was defined as the yield strength. The obtained yield strength of each test number is shown in Table 3 as "YS (MPa)".
[0126] [Table 3]
[0127] [Fn2 measurement test] For each seamless steel pipe of each test number, the prior γ grain size D (μm), grain boundary Mn content [Mn] (mol%), grain boundary P content [P] (mol%), grain boundary Mo content [Mo] (mol%), and Fn2 (-0.0851×D-[Mn]-3×[P]+[Mo]) calculated from the above definition were calculated using the above method. Specifically, a test piece for measuring the prior γ grain size D was prepared from the center of the wall thickness of each seamless steel pipe of each test number, with the surface including the pipe axis direction and the pipe diameter direction as the observation surface. The prepared test piece was embedded in resin, and the observation surface was polished to a mirror finish, and then immersed in a solution of a saturated aqueous solution of picric acid mixed with an appropriate amount of surfactant for about 60 seconds to reveal the prior γ grain boundaries by etching. The etched 100 mm 2 The observation surface (10 mm × 10 mm) was observed with an optical microscope, and the grain size number was determined based on the cutting method in accordance with JIS G 0551 (2020). Using the obtained grain size number, the prior austenite grain size (prior gamma grain size D) was determined by the method described above.
[0128] Next, notched round bar test pieces were prepared from each seamless steel pipe by the above-mentioned method. The test pieces cooled to -120°C or lower by the above-mentioned method were placed in a vacuum chamber with a degree of vacuum of 10 -7 The specimen was fractured in a chamber at or below 100 Pa, and three prior-γ grain boundary fracture surfaces were obtained. Three measurement points were identified on each of the three prior-γ grain boundary fracture surfaces, for a total of nine measurement points. The measurement points were identified in areas of the prior-γ grain boundary fracture surfaces other than the precipitates. When three prior-γ grain boundary fracture surfaces could not be obtained from one test specimen, the three prior-γ grain boundary fracture surfaces were obtained using multiple test specimens.
[0129] For each measurement point, element concentration analysis by Auger electron spectroscopy was performed by the above-mentioned method to quantify the contents of P, S, C, Cr, Fe, Mn, Si, and Mo. The arithmetic average value of the Mn content (mol.%) when the total content of P, S, C, Cr, Fe, Mn, Si, and Mo was taken as 100 mol.% was obtained as the grain boundary Mn content [Mn] (mol.%). Similarly, the arithmetic average value of the P content (mol.%) when the total content of P, S, C, Cr, Fe, Mn, Si, and Mo was taken as 100 mol.% was obtained as the grain boundary P content [P] (mol.%). Furthermore, the arithmetic average value of the Mo content (mol.%) when the total content of P, S, C, Cr, Fe, Mn, Si, and Mo was taken as 100 mol.% was obtained as the grain boundary Mo content [Mo] (mol.%).
[0130] The prior γ grain size D (μm) obtained is shown in Table 3 as "D (μm)". Similarly, the grain boundary Mn content [Mn] (mol%), grain boundary P content [P] (mol%), and grain boundary Mo content [Mo] (mol%) obtained are shown in Table 3. Furthermore, Fn2 was calculated. The obtained Fn2 is shown in Table 3.
[0131] [SSC resistance evaluation test] The seamless steel pipes of each test number were subjected to an SSC resistance evaluation test by the above-mentioned method. Specifically, the SSC resistance test was performed on three round bar test pieces prepared by the above-mentioned method in accordance with NACE TM0177-2016 Method A. The axial direction of the test pieces was parallel to the pipe axial direction. A tensile stress equivalent to 90% of the axial yield stress was applied in the axial direction of the round bar test pieces of each test number. The test solution used was a 5.0 mass% sodium chloride aqueous solution (NACE solution A) adjusted to pH 2.7 with acetic acid.
[0132] The test solution at 24°C was poured into each of the three test vessels to form the test bath. The three round bar test specimens to which stress had been applied were immersed one by one in the test bath in a different test vessel. After degassing each test bath, 1 atm of H2S gas was blown into the test bath to saturate it. The test bath saturated with 1 atm of H2S gas was held at 24°C for 720 hours. After 720 hours of holding, the round bar test specimens of each test number were observed for the occurrence of sulfide stress cracking (SSC). Specifically, the round bar test specimens after 720 hours of holding were observed with the naked eye. As a result of the observation, specimens in which no cracks were found in any of the three test specimens were judged to be "EX" (Excellent). On the other hand, specimens in which cracks were found in at least one test specimen were judged to be "NA" (Not Acceptable).
[0133] [Evaluation Results] With reference to Tables 1-1, 1-2, 2, and 3, the seamless steel pipes of test numbers 1 to 39 had appropriate chemical compositions, Fn1 satisfied 0.045 to 0.200, and the manufacturing method also satisfied the preferred conditions described in the specification. As a result, these seamless steel pipes had a yield strength of 552 to less than 655 MPa and had a yield strength of 80 ksi. These seamless steel pipes further satisfied Fn2 of -13.1 or more. As a result, these seamless steel pipes were evaluated as "EX" in the SSC resistance evaluation test, and had excellent SSC resistance. It was determined that the total volume fraction of tempered martensite and tempered bainite was 90% or more for all of these seamless steel pipes.
[0134] On the other hand, the seamless steel pipe of test number 40 had an excessively low C content, and as a result, the seamless steel pipe had a yield strength of less than 552 MPa, and did not have a yield strength of 80 ksi.
[0135] The seamless steel pipe of test number 41 had an excessively low Mn content, which resulted in the seamless steel pipe having a yield strength of less than 552 MPa, and thus did not have a yield strength of 80 ksi.
[0136] The seamless steel pipe of test number 42 had too high a Mn content. Furthermore, Fn2 was too low. As a result, this seamless steel pipe was rated "NA" in the SSC resistance evaluation test, and did not have excellent SSC resistance.
[0137] The seamless steel pipe of test number 43 had too high a P content. Furthermore, Fn2 was too low. As a result, this seamless steel pipe was rated "NA" in the SSC resistance evaluation test, and did not have excellent SSC resistance.
[0138] The seamless steel pipe of test number 44 had an excessively high S content. As a result, this seamless steel pipe was rated "NA" in the SSC resistance evaluation test, and did not have excellent SSC resistance.
[0139] The seamless steel pipe of test number 45 had an excessively low Cr content, and as a result, the seamless steel pipe had a yield strength of less than 552 MPa, which was not of the 80 ksi class.
[0140] The seamless steel pipe of test number 46 had an excessively high Cr content, which resulted in the seamless steel pipe having a yield strength of 655 MPa or more, which was not of the 80 ksi class.
[0141] The seamless steel pipe of test number 47 had too high Mo content. In addition, Fn1 was too high. As a result, the seamless steel pipe had a yield strength of 655 MPa or more, which was not 80 ksi-class yield strength.
[0142] The seamless steel pipe of test number 48 had a holding temperature T (℃) in the tempering holding step that was too low. As a result, the seamless steel pipe had a yield strength of 655 MPa or more, which was not of the 80 ksi class.
[0143] The seamless steel pipe of test number 49 was heated at a rate of 500℃ to T1 (℃) at HR 500-T1 (°C / min) was too slow. As a result, Fn2 was too low. As a result, this seamless steel pipe was rated "NA" in the SSC resistance evaluation test, and did not have excellent SSC resistance.
[0144] The seamless steel pipe of test number 50 is heated at a rate of T1 (℃) to T (℃) HR T1-T (°C / min) was too fast. As a result, Fn2 was too low. As a result, this seamless steel pipe was rated "NA" in the SSC resistance evaluation test, and did not have excellent SSC resistance.
[0145] The seamless steel pipe of test number 51 was cooled at a rate of T(℃) to T1(℃) CR T-T1 (°C / min) was too fast. As a result, Fn2 was too low. As a result, this seamless steel pipe was rated "NA" in the SSC resistance evaluation test, and did not have excellent SSC resistance.
[0146] The seamless steel pipe of test number 52 was subjected to a cooling rate of T1 (℃) to 500℃. T1-500 (°C / min) was too slow. As a result, Fn2 was too low. As a result, this seamless steel pipe was rated "NA" in the SSC resistance evaluation test, and did not have excellent SSC resistance.
[0147] The seamless steel pipes of test numbers 53 and 54 had too high Fn1. As a result, these seamless steel pipes had a yield strength of 655 MPa or more, which was not of the 80 ksi class.
[0148] The seamless steel pipes of test numbers 55 and 56 had too low Fn1, and as a result, the seamless steel pipes were rated "NA" in the SSC resistance evaluation test and did not have excellent SSC resistance.
[0149] The embodiments of the present disclosure have been described above. However, the above-described embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above-described embodiments, and can be implemented by appropriately modifying the above-described embodiments without departing from the spirit of the present disclosure.
Claims
1. A steel material, In mass percent, C: 0.26-0.35%, Si: 0.10-1.00%, Mn: 0.90-1.40%, P: 0.015% or less, S: 0.0020% or less, Cr: 0.15-0.50%, Mo: 0.05-0.25%, sol. Al: 0.001 to 0.070%, N: 0.0010-0.0080%, V: 0-0.60%, Nb: 0 to 0.03%, Ti: 0 to 0.05%, W: 0-0.50%, Zr: 0 to 0.005%, Co: 0 to 0.500%, Ni: 0-0.300%, Cu: 0-0.500%, Sn: 0-0.100%, Ca: 0-0.0035%, Mg: 0 to 0.0035%, B: 0 to 0.0010%, Rare earth elements: 0 to 0.0050%, and The balance is composed of Fe and impurities and satisfies formula (1); The yield strength is less than 552 to 655 MPa; In the steel material, The prior austenite grain size is defined as D, When the Mn content in the vicinity of the prior austenite grain boundary is defined as [Mn], the P content in the vicinity of the prior austenite grain boundary is defined as [P], and the Mo content in the vicinity of the prior austenite grain boundary is defined as [Mo], The D, the [Mn], the [P], and the [Mo] satisfy formula (2); Steel material. 0.045≦Mo / Mn≦0.200 (1) -0.0851×D-[Mn]-3×[P]+[Mo]≧-13.1 (2) Here, the element symbols in formula (1) are substituted with the contents of the corresponding elements in mass %, the prior austenite grain size is substituted for D in formula (2) in μm, the Mn content in the vicinity of the prior austenite grain boundaries is substituted for [Mn] in formula (2) in mol %, the P content in the vicinity of the prior austenite grain boundaries is substituted for [P] in formula (2) in mol %, and the Mo content in the vicinity of the prior austenite grain boundaries is substituted for [Mo] in formula (2) in mol %.
2. The steel material according to claim 1, V: 0.01-0.60%, Nb: 0.01-0.03%, Ti: 0.01-0.05%, W: 0.01-0.50%, Zr: 0.001 to 0.005%, Co: 0.001 to 0.500%, Ni: 0.001-0.300%, Cu: 0.001 to 0.500%, Sn: 0.001 to 0.100%, Ca: 0.0001-0.0035%, Mg: 0.0001 to 0.0035%, B: 0.0001 to 0.0010%, and Rare earth elements: 0.0001 to 0.0050%; containing one or more elements selected from the group consisting of Steel material.
3. The steel material according to claim 1 or 2, The steel material is a steel pipe. Steel material.
Citation Information
Patent Citations
Steel pipe for oil well having excellent collapse strength, and testing method thereof
JP2002115028A